Development of Moocs-Assisted Digital Teaching Materials to Improve Students' Learning Motivation in Business and Energy Materials at Senior High School of Bengkulu City - Lola Dwi Syafitri (CV Media Inti Teknologi, 2023)
The purpose of this study was to see students' perceptions of MOOCs-assisted digital teaching materials for work and energy materials. This research uses the research and development (R&D) method and uses the 4D model. The population in this study were high school students in Bengkulu city with a sample of class XI high school students who were in three schools in Bengkulu, namely SMAN 4 Bengkulu City, SMAN 9 Bengkulu City, and SMAN 10 Bengkulu City. The research was conducted from August to November. The research was conducted using a Liket scale instrument, observation sheets, interview sheets, and needs questionnaire sheets. Data collection techniques were also carried out by observation, interviews, and questionnaires. Data analysis was carried out quantitatively with the help of SPSS. This study obtained the result that the current teaching materials are very boring, just printed books. Thus, 78.25% of respondents agree that digital teaching materials are very necessary to increase student learning motivation.